Study Of Community Based Agrotourism And Land Carrying Capacity In Kalisentul, Kalibawang, Kulon Progo - Resna Trimerani; Ismiasih Ismiasih; Alan Handru (UNIVED Press, Dehasen University Bengkulu, 2025)
Purpose: To study the potential of Agrotourism in the Kalisentul Area, where in its implementation it begins with the identification of agricultural potential in Kalisentul which has the potential to be developed into an Agrotourism Area. The land conditions in Kalisentul have the characteristics of sloping land but in some parts have flat and wide land so that it can be used for agricultural activities. Methodology: using a survey method with a descriptive approach, so that it can explain the results of the identification of agricultural potential and explain the phenomena found in the Kalisentul community. Location surveys and area plotting have been carried out to determine the agrotourism area, planning for agricultural-based tourism event training and training in cultivating fruit and vegetables. Results: This study provides results that the potential for developing an Agrotourism Area in Kalisentul Village, after analyzing the planning and design concepts, is very large and profitable which is supported by the active participation of the community, the availability of extensive land and support from the government and/or private parties. Findings: The results of this study are certainly supported by the potential of natural resources owned by Kalisentul so that it can be developed into an Agrotourism Area. Novelty: Based on the research results, Kalisentul has good land carrying capacity in the development of Agrotourism Areas, where the form of Agrotourism that can be developed is agricultural education, especially horticultural plants. Originality: The uniqueness of this area is the existence of land and natural resources that are still very feasible to be developed into an Agrotourism Area and the existence of good community participation in its management. Conclusion: The Kalisentul area is feasible to be developed into an Agrotourism Area based on agricultural education. Output: The results of this study were published in the SINTA Accredited National Journal.